Fixed screw-retained interim restorations with immediate implant placement in esthetic zone: A case series with six different techniques - Udatta Kher; Pravinkumar G Patil; Ali Tunkiwala; Smita Nimbalkar (The Journal of Indian Prosthodontic Society, 2022)
Postextraction immediate implant placement in the esthetic zone is a common treatment modality. Immediate fixed interim restoration following immediate implant placement may provide excellent esthetic results to the patients and boost the clinicians' confidence. This paper demonstrates a series of six different techniques used to fabricate the customized screw-retained interim restorations following immediate implant placement with partial extraction therapy in the maxillary anterior esthetic zone. The techniques have utilized a putty index, polycarbonate shell crown, patients' existing crowns (prosthetic or natural), or laminate veneer, or fabricated in the laboratory based on the specific clinical situation. Advantages and limitations of each technique including alternative techniques or materials have been discussed. Excellent esthetic results were obtained with all six techniques using the screw-retained immediate interim restorations following partial extraction therapy and immediate implant placement.